Circulating Maresin-1 and cartilage remodeling biomarkers in rheumatoid arthritis and osteoarthritis - Esmez, Omer; Deniz, Gulnihal; Ercan, Zubeyde; Yilmaz, Secil; Dogru, Meryem Sedef; Karatas, Ahmet (Nature Portfolio, 2026)
Rheumatoid arthritis (RA) and osteoarthritis (OA) are prevalent chronic joint diseases characterized by persistent inflammation, progressive cartilage degeneration, and impaired tissue repair mechanisms. While inflammatory pathways have been extensively studied, increasing attention has been directed toward the failure of inflammation resolution as a key contributor to chronic joint pathology. Specialized pro-resolving mediators (SPMs), including Maresin-1 (MaR1), play an active role in terminating inflammation and promoting tissue homeostasis. However, the relationship between MaR1 and cartilage-specific biomarkers such as Cartilage Oligomeric Matrix Protein (COMP) and Wnt1-inducible signaling pathway protein-1 (WISP-1) has not been sufficiently elucidated. This study investigated circulating MaR1 levels in RA and OA and examined their associations with serum COMP and WISP-1 as well as clinical inflammatory parameters. This cross-sectional, biomarker-based study included a total of 150 participants, comprising 50 patients with RA, 50 patients with OA, and 50 sex-matched healthy controls. Serum levels of MaR1, COMP, and WISP-1 were measured using enzyme-linked immunosorbent assay (ELISA). Demographic characteristics and inflammatory parameters, including erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and rheumatoid factor (RF), were recorded. Intergroup comparisons were performed using one-way analysis of variance (ANOVA) followed by appropriate post-hoc tests. Serum MaR1 levels were significantly reduced in both RA (44.1 +/- 2.2 ng/L) and OA (42.2 +/- 3.2 ng/L) compared with controls (78.5 +/- 7.5 ng/L; p < 0.001). COMP levels were significantly lower in the RA group than in the OA and control groups (p < 0.05 and p < 0.001, respectively). Similarly, WISP-1 concentrations were decreased in both RA and OA compared with healthy controls (p < 0.05). The marked reduction in MaR1 levels in RA and OA is consistent with altered inflammation-resolution biology. Concurrent decreases in COMP and WISP-1 may reflect changes in cartilage remodeling dynamics. Overall, MaR1 appears to be a candidate biomarker associated with inflammation-resolution pathways in arthritic diseases.
Keywords: Maresin-1; Rheumatoid Arthritis; Osteoarthritis; Cartilage Oligomeric Matrix Protein; Wisp-1; Biomarker